Pengelolaan BOS Smp Negeri 1 Simo dalam Mekanisme APBD Pemerintah Kabupaten Boyolali Tahun 2011 - Siswanto, Siswanto; Sutrisna, Budi (Universitas Muhammadiyah Surakarta, 2014)
The focus of this research is the management of School Service Funding inJunior High School 1 of Simo. The objectives of this research are to describe the planning, implementation and the reporting of School Service Funding in Junior High School 1 of Simo on the Revenue and Expenditure Budget Mechanism of Boyolali Regency on 2011.The design of this research is ethnography. The location of this research is in Junior High School 1 of Simo. The informants in this research are the principal, the teachers, the school committee and the students. The methods of collecting data in this research are 1) in depth interview the principal, the teachers, the school committee and the students, 2) active observation and 3) documentation. Data analyze is using Interactive Analyze Model. Data validity is used sources triangulations and methods triangulations.The results of this research are 3. 1) the team management of School Service Funding made planning with the committee according to the national education standard which the priority on the routine cost. 2) the cost with School Service Funding was according on the instruction and applying cross subsidy. 3) the cost with School Service Funding was supported with payment check and goods, made on reports and announced written and oral.